PENGARUH ZAKAT PRODUKTIF TERHADAP KESEJAHTERAAN MUSTAHIK DI LEMBAGA YATIM MANDIRI - Ivon Novita Ramadhani (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
Poverty is a big problem that is certainly experienced in developing countries, one of which is Indonesia. This means that poverty is a condition of someone unable to meet their basic needs. Well-being is something that can be felt by someone in their life where they feel their lives are fulfilled and fulfilled without any burden and pressure. So that this zakat will provide more benefits for the community and reduce poverty in Indonesia. Zakat is one of the pillars of Islam that must be carried out by every Muslim to purify themselves which is done once a year, the involvement of zakat in this research has the aim of reducing poverty in Indonesia. Where the zakat funds obtained by these mustahik help beneficiaries in managing their businesses. This study analyzes the effect of productive zakat on the welfare of mustahik by comparing the level of income before and after receiving zakat funds for mustahik. This study uses quantitative research methods using primary data and questionnaire tools. Then the sample taken by the researcher was 10 mustahik using a random sampling technique. The results of this study have a significant influence on productive zakat on the welfare of mustahik. Where mustahik's income has increased before and after receiving productive zakat. Keywords: Productive Zakat, Mustahik Welfare references Bappeda Jatim. “Presentasi Penduduk Miskin Jatim 2022 Maret”. http://bappeda.jatimprov.go.id BAZNAS “Potensi Zakat Di Indonesia”. http://bisnis.tempo.co. Dian Ghani Reza Dasangga, Eko Fajar Cahyono. “Analisis Peran Zakat Terhadap Pengentasan Kemiskinan Dengan Model Cibest (Studi Kasus Rumah Gemilang Indonesia Kampus Surabaya).” Jurnal Ekonomi Syariah Teori dan Terapan Vol.7 No.6 (2020):1060-1073. Fasiha. “ Alternatif Sistem Pengendalian Kemiskinan” Buku Zakat Produktif Fatmawati. “Penyaluran Zakat Kepada Fakir Miskin Dalam Upaya Mengentaskan Kemiskinan (Study Pada Lembaga Amil Zakat Daerah PKPU DIY). Hendra Maulan. “Analisa Distribusi Zakat Dalam Meningktakan Kesejahteraan Mustahik”. (Studi Pada BAZ Kota Bekasi). Kirana Sasadhara. “Pengaruh Dana Zakat Produktif Terhadap Kesejahteraan Mustahiq (Sudi Pada Program Jatim Makmur BAZNAS Provinsi Jawa Timur). Latifvah Permata Zandri. “Analisis Pendayagunaan Zakat Produktif Dalam Meningkatkan Kekesjahteraan Mustahiq Berdasarkan Cibest Model Pada IZI Yogyakarta Dan LAZIZ YBW UII.” Ningsih Andriani. “Pengaruh Pemanfaatan Dana Zakat Produktif Terhadap Tingkat Pendapatan Mustahiq Pada BAZNAS Kota Makassar.” Rachmad Dharmawan. “ Zakat Produktif Dalam Keberhasilan Usaha Mustahik”, (Studi kasus LAZ Inisiatif Zakat Indonesia Cabang Jawa Timur). Vol.6 No.11 (2019)